Chronology of Records of Harder Run in Uzbekistan and in the World - Kh.X.Boimatov (Global Scientific Publishing, 2022)
This article reflects the chronology of the reсords of track and field athletes who specializes in hurdles on the scale of Uzbekistan and the world at distances of 100, 110 and 400 meters. Attention is paid to the manual stopwatch and electronic detection methods used to determine the result of athletes during the competition. It also contains information about records set by athletes in running, but not taken into account. The article is enriched with information from recent history, which concerns the determination of the results of hurdling.
Keywords: Hurdling; stopwatch; athletes; chronometer